Experimental Bonfirings of Pottery with Camel Dung Fuel, Jordan, July 2018 - Maria-Louise Sidoroff (EXARC Journal)
The objective of this series of experimental pottery firings with camel dung fuel was to isolate the function of this fuel type within the context of a simple mode of pottery firing for data applicable to studies of ancient pottery manufacture.